Needs analysis of a sexuality education program for the prevention of sexual violence - Maurra S. Wijaya; Rudi Susilana; Riksma Nurahmi Rinalti Akhlan (Universitas Pendidikan Indonesia, 2025)
Sexuality education at the elementary school level is a crucial preventive measure to protect children from sexual violence. However, its implementation in Indonesian schools remains informal, unstructured, and often confined to moral-religious discourses lacking scientific and psychosocial grounding. This study aims to analyze competency needs as a foundation for developing a school-based sexuality education program grounded in local contexts. Employing a sequential exploratory mixed-methods design, the study began with in-depth interviews involving program implementer teachers and the vice principal for curriculum affairs, followed by a competency-based survey. The findings reveal a strong awareness of the urgency of sexuality education. Significant challenges persist—namely, limited teacher capacity, the absence of structured modules, and time constraints within school routines. Despite these obstacles, school leadership support, teacher openness, and positive parental responses provide a strong foundation for future program development. This study offers a novel contribution by applying a needs-based lens and identifying the implementation gap between global recommendations and local realities, particularly within faith-based school settings. By focusing on local insights within an Islamic school context, this research provides contextually grounded, empirically informed input for curriculum design—bridging the divide between normative recommendations and practical realities in Indonesian schools. Abstrak Pendidikan seksualitas pada jenjang sekolah dasar merupakan langkah preventif yang sangat penting dalam upaya perlindungan anak dari kekerasan seksual. Namun, implementasinya di Indonesia masih bersifat informal, tidak terstruktur, dan kerap berbasis pada pendekatan moral-religius yang minim aspek ilmiah dan psikososial. Penelitian ini bertujuan untuk menganalisis kebutuhan kompetensi sebagai dasar pengembangan program pendidikan seksualitas di sekolah dasar berbasis kebutuhan kontekstual. Penelitian ini menggunakan metode campuran eksplanatori (sequential exploratory mixed-method) dengan pendekatan kualitatif pada tahap awal melalui wawancara mendalam dengan guru pelaksana program dan wakil kepala sekolah bidang kurikulum, dilanjutkan dengan survei kompetensi. Hasil menunjukkan adanya kesadaran tinggi akan pentingnya pendidikan seksualitas, namun dihadapkan pada tantangan berupa keterbatasan kapasitas guru, ketiadaan modul baku, serta kendala waktu dalam pelaksanaan program. Meski demikian, dukungan dari pimpinan sekolah, keterbukaan guru, dan respons positif dari orang tua menjadi modal awal penting untuk mengembangkan program yang sistematis. Penelitian ini menyumbang kebaruan dengan menawarkan pendekatan berbasis kebutuhan dan mendeskripsikan kesenjangan antara norma global dan praktik lokal dalam konteks sekolah berbasis nilai agama. Dengan berfokus pada wawasan lokal dalam konteks sekolah Islam, penelitian ini memberikan masukan yang berlandaskan konteks dan berdasarkan pengalaman untuk desain kurikulum—menjembatani kesenjangan antara rekomendasi normatif dan realitas praktis di sekolah-sekolah Indonesia. Kata Kunci: kekerasan seksual; pendidikan seksualitas; pengembangan kurikulum pendidikan seksualitas; sekolah dasar